Hubungan Berat Badan Lahir, Asi Eksklusif, dan Gizi Makanan dengan Stunting pada Anak - Hendrayani, Ayu Ekanita; Widati, Sri; Widjaja, Nur Aisiyah (Journal of Telenursing (JOTING), 2023)
This study aims to determine the relationship between Birth Weight, Exclusive Breastfeeding, and Nutritional Intake with stunting in children. The method used in this research employs a quantitative approach. The sample in this study consists of 40 toddlers. The variables in this research include Birth Weight, Exclusive Breastfeeding, and Nutritional Intake as independent variables, and stunting in children as the dependent variable. The instrument used is a questionnaire consisting of questionnaires to be filled out, and the data analysis conducted in this research utilizes regression model testing. The results of the research indicate that Birth Weight has a significant relationship with stunting in children, with a coefficient of determination of 73.7%; Exclusive Breastfeeding has a significant relationship with stunting in children, with a coefficient of determination of 73.4%; and Nutritional Intake has a significant relationship with stunting in children, with a coefficient of determination of 72.3%. The conclusion of this study is that the occurrence of stunting in children can be associated with several factors such as low birth weight, exclusive breastfeeding, and nutritional intake provided to the child during the child's growth period, which are factors related to the occurrence of stunting in children. Keywords: Exclusive Breastfeeding, Food Nutrition, Low Birth Weight, Stunting.